Pengembangan Bahan Ajar Pop Up Book Materi Pergerakan Kebangsaan Menuju Kemerdekaan Kelas VIII MTs Darussalam Kademangan - Safina Rahma Aulia; Hendra Pratama (KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of the study is to determine the level of validity and effectiveness of the pop up book teaching aid covering the topic of the national movement toward independence for Grade VIII students at MTs Darussalam Kademangan. The study employed the Research and Development (R&D) method with the Borg and Gall model. The main subject in this study were students in class VIII E MTs Darussalam Kademangan with a total of 31 students. The results of this study indicate that the results of the media expert validation test were 90%, the material expert validation was 95%, and the subject social studies teacher validation was 95%. The results of the efeectiveness test conducted using a Paired Sample T-test yielded a significance value of 0.000, wich is less than 0.05. Thus, the alternative hypothesis is declared accepted indicating a significant difference in students learning outcomes before and after using the pop up book teaching aid. So, it can be concluded that the pop up book teaching aid on the national movement toward independence is valid according to experts and effective in improving student learning outcomes.